Cardiotoxicity Evaluation of Tyrosine Kinase Inhibition using Human Induced Pluripotent Stem Cell-derived Healthy and Long QT Syndrome Cardiomyocytes - Zhao, Qi; Zhang, Yizhe; Zhang, Yuqing; Teng, Yiyang; Yang, Shuwen; Yang, Hao; Xing, Hongyan; Wang, Xijie (Archives of Clinical and Biomedical Research, 2024)
Tyrosine kinase inhibitors (TKIs) are small-molecule targeted therapy drugs that play an important role in the treatment of hematological malignancies and solid tumors. Drug-induced cardiotoxicity in both preclinical studies and clinical trials has been reported, whereas the toxicity in populations with congenital electrophysiological dysfunction remains unclarified. Hence, an investigation of TKIs toxicological research helps assess the drug response in patients, predicting cardiotoxicity risk, and providing a reference for clinical application. We investigate the cardiotoxicity of four tyrosine kinase inhibitors (Crizotinib, Sunitinib, Dasatinib, and Lapatinib) with different targets using cardiomyocytes differentiated from disease-specific human-induced pluripotent stem cells derived from WT- and Long QT syndrome patient (WT- and LQT-hiPSC-CMs) combined with real-time cell analysis (RTCA), immunofluorescence, and chemiluminescence. In this study, Crizotinib, Sunitinib, and Lapatinib caused cardiotoxicity by reducing contractility, damaging the cell structure, and activating the Caspase-3/7 pathway supply. Dasatinib showed a lower risk of cardiotoxicity compared with the other three candidates. Compared with WT-hiPSC-CMs, LQT-hiPSCCMs showed a higher sensitivity to Crizotinib and Sunitinib-induced cardiotoxicity. Our study indicates that congenital channelopathies, such as LQTs, may predispose patients to even higher risks, which require particular monitoring for the occurrence of adverse cardiac events.